The role of NLRP3 inflammasome in digestive system malignancy - Sun, Cen-Cen; Li, Li; Tao, Hou-Quan; Jiang, Zhi-Chen; Wang, Liang; Wang, Hui-Ju (Frontiers in Cell and Developmental Biology, 2022)
Digestive system malignancy, the most common types of cancer and a major cause of death in the worldwide, is generally characterized by high morbidity, insidious symptoms and poor prognosis. NLRP3 inflammasome, the most studied inflammasome member, in considered to be crutial in tumorigenesis. In this paper, we reviewed its pro-tumorigenic and anti-tumorigenic properties in different types of digestive system malignancy depending on the types of cells, tissues and organs involved, which would provide promising avenue for exploring new anti-cancer therapies.